Implementasi Business Process Re-Engineering pada Pengelolaan Perbekalan Farmasi pada Rumah Sakit Ibu dan Anak (RSIA) Kota Malang - Renny Dwi Ning Istyana; A. Rohendi; Oke Andikarya (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
The availability of pharmaceutical supplies in hospitals is a basic requirement must be maintained, because medicine and pharmaceutical supplies are one of the factors that influence health care in hospitals. Pharmaceutical product management is a complex process. Inefficient management has a negative impact on hospital operational costs. Business Process Reengineering (BPR) is an effort to improve or refinement strategies by utilizing technology in the form of SIM- RS to increase productivity, effectiveness and efficiency in managing pharmaceutical supplies. This study aims to determine the implementation of BPR in the management of pharmaceutical supplies in pharmaceutical installations in hospitals. The method used is descriptive qualitative by conducting natural observations and interviews. The interview results were then reduced, analyzed and the data were presented in narrative form accompanied by tables and graphs. The size of the population consists of eight informants included director of the hospital, pharmaceutical procurement staff, finance managers, IT staff, pharmacist and nursing service staff, pharmaceutical procurement staff of external hospital as an informer triangulation. The results showed that the implementation of BPR can reduce the costs of managing pharmaceutical supplies by up to 70%, linear purchase and sales graphs, and researchers can find out the success factors in implementing BPR. It is important for organizations to have specific and detailed standard operating procedures so that BPR can implemented according to vision and goals.